(untitled) (Bioscience Journal, 2015)
The focus of this study was to test the fracture resistance of upper arch dental retainers, made by two different manipulation techniques of acrylic resin. 84 plates Wraparound type retainers were made by two different manipulation techniques forming two groups (n = 42): Group 1 (Addition Technique) and Group 2 (Pressing Technique). All the retainers were duly shaped in U form with the aid of standardized plaster cast models. During the confection process the standardizing of the retainers was conducted carefully regarding their thickness and dimensions with the aid of a gauge and a straight caliper. After confection they remained immersed in water for 24 hours at 37°C. Next, they were tested through mechanical compression until fracture in a universal mechanical testing machine. Data were analyzed by Student’s t test. The significance level was set at 5% (Î± = 0.05). It was found that the average was of 79.12 N for Group 1 and of 77.07 N for Group 2 with a standard deviation of 17.30 N and 16.31, respectively, showing that there is no significant difference in resistance for the retainers when made through any of the two methods (P=0.788). The addition and pressure techniques of acrylic resin do not influence the resistance to compression of the upper dental retainers.